Asymptotic behavior of first order delay difference equation with a forcing term - Murugesan, A.; Venkataramanan, K. (International Journal of Applied Mathematical Research, 2015)
In this paper, we study the asymptotic behavior of solutions of the following first order forced delay difference equation equation*Δ x(n)+p(n)f(x(n-τ))+r(n)=0,n≥ 0. Â (*)equation* Some sufficient conditions for every solution of (*) to tend to zero are established.